Переработка скрапа твердых сплавов группы ВК (обзор) - Бондаренко, В.П.; Мартынова, Л.М.; Галков, А.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The review of publications on WC–Co cemented carbide scrap recycling methods is presented. The advantages and disadvantages of different recycling methods, the requirements to scrap and the quality of the resulting products are analyzed.